ANALISIS FAKTOR ASSURANCE IN SERVICE TERHADAP KEPUASAN WISATAWAN PENGGUNA JASA BIRO PERJALANAN WISATA DI BALI - Made Sudiarta (JURNAL KEPARIWISATAAN, 2009)
This research is focused on the influence of service dimension to tourists' satisfaction concerning the service provided by travel agencies in Bali. The researched factors are those which closely related to services, in particular to tourism service. It is especially for tourism service that was developed by Parasuraman as one of the service dimensions such as assurance observed by six variables. Confirmatory factor analysis is used in this research, in which processed through validity and reliability test, Keiser Meyer Olkin (KMO) and Bartlett's Test. The result of research indicates that all the variables have significant validity and reliability level by alpha Cronbach value of more than 0.600. Keiser Meyer Olkin and Bartlett's Test indicate that all variables used in this research are relevant to the model by the value of more than 0,05. The variable of the analyzed service dimension which gives the strongest influence to the services provided by travel agency in Bali is quick and friendly service. From overall satisfaction point of view, it is obtained that tourists who use the travel agency's services during their trip in Bali are factually satisfied. As the indicators observed in this research show that travel agencies in Bali are able to conduct good service to tourists or visitors